The Achievement-Driven Coaching Management Of Early-Age Football Sport At Tunas Muda Football School In Bengkulu City - Ferdiansah, Rahmad; Kristiyanto, Agus; Riyadi, Slamet (Journal of Education, Health and Sport, 2019)
The present study aimed at deeply eliciting information vis-a-vis the achievement-driven coaching management of early-age football sport at Tunas Muda football school in Bengkulu City specifically in terms of planning, organizing, directing, and monitoring. Tunas Muda football school was established in 2009, and its existence has been admitted up to nowadays. Of several football schools in Bengkulu, Tunas Muda Football School was found to be very active and to have lots of achievements at both regional and national level. This study applied a mixed-method approach. The techniques of collecting data in this study were comprised of questionnaire, interview, observation, and documentation. The results revealed that the achievement-driven coaching management undertaken by Tunas Muda football school in Bengkulu especially in the aforementioned four aspects had been running properly. In addition, the statistical data also supported the results, wherein in the management the most protuberant factor was planning with the percentage of 92%, while other factors subsumed organizing with the percentage of 84 %, directing with the percentage of 84%, and monitoring with the percentage of 83%. Those factors were all classified as very good.